2010
DOI: 10.1017/s1743921311015602
|View full text |Cite
|
Sign up to set email alerts
|

Helioseismic probing of the subsurface structure of sunspots

Abstract: Abstract. We discuss recent progress in the helioseismic probing of the subsurface structure of solar magnetic regions. To simulate the interaction of helioseismic waves with magnetic fields and thermal perturbations we use a simple model that is translation invariant in the horizontal directions, has a realistic stratification in the vertical direction, and has physically consistent boundary conditions for the waves at the upper and lower boundaries of the computational domain. Using this model we generate sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The study, however, found a major disagreement between the model and measured travel-time shifts. Since an earlier hare and hound analysis of simulated data containing only pure sound speed perturbation had shown remarkable agreement between the model and measured shifts (Birch et al, 2011), it is believed that the inclusion of the magnetic field in the sunspot simulation has caused the disagreement in the travel-time shifts. Thus, it is conjectured that the inversion methods which incorporate direct effects of the magnetic field (Crouch et al, 2011), including mode conversion are required to make further progress.…”
Section: Forward Modeling and Numerical Simulationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The study, however, found a major disagreement between the model and measured travel-time shifts. Since an earlier hare and hound analysis of simulated data containing only pure sound speed perturbation had shown remarkable agreement between the model and measured shifts (Birch et al, 2011), it is believed that the inclusion of the magnetic field in the sunspot simulation has caused the disagreement in the travel-time shifts. Thus, it is conjectured that the inversion methods which incorporate direct effects of the magnetic field (Crouch et al, 2011), including mode conversion are required to make further progress.…”
Section: Forward Modeling and Numerical Simulationsmentioning
confidence: 97%
“…Since an earlier hare and hound analysis of simulated data containing only pure sound speed perturbation had shown remarkable agreement between the model and measured shifts (Birch et al, 2011), it is believed that the inclusion of the magnetic field in the sunspot simulation has caused the disagreement in the travel-time shifts. Thus, it is conjectured that the inversion methods which incorporate direct effects of the magnetic field (Crouch et al, 2011), including mode conversion are required to make further progress. Developing an inversion method which can account for the complicated influence of the strong magnetic fields on travel-time shifts remains a challenge for sunspot seismology.…”
Section: Forward Modeling and Numerical Simulationsmentioning
confidence: 97%
“…( 2012) demonstrated that standard modeling efforts, assuming only a perturbation to wave speed, do not reproduce the expected travel time signatures. It is suggested that the inversion methods which incorporate direct effects of the magnetic field, including mode conversion (Crouch et al 2011), are required to make further progress. The study of Cally & Moradi (2013) indicated that the propagating fast and Alfvén waves introduce a significant travel time shift that The figure demonstrates that the magnitude of δτ strongly depends on frequency and magnetic field inclination.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Numerical simulations have provided artificial data through which helioseismic analysis and modeling can be tested (Jensen et al, 2003;Benson, Stein, and Nordlund, 2006;Hanasoge et al, 2006;Parchevsky and Kosovichev, 2007;Zhao et al, 2007;Braun et al, 2007;Cameron, Gizon, and Duvall, 2008;Parchevsky and Kosovichev, 2009;Crouch et al, 2010;Cameron et al, 2011;Birch et al, 2011;Hartlep et al, 2011;Braun et al, 2012). Many of these simulations include near-surface flows, sound-speed perturbations, or magnetic structures typical of active regions or supergranulation.…”
Section: Introductionmentioning
confidence: 99%